Pengembangan Media Interaktif Berbasis Ispring Suite pada Mata Pelajaran IPAS Kelas IV SD Negeri 106189 Sennah - Detristia, Debby; Simanihuruk, Lidia; M, Zainuddin; Mailani, Elvi; Rozi, Fahrur (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this study was to describe the feasibility, practicality, and effectiveness of interactive media based on Ispring Suite in the subject of science for grade IV of SD Negeri 106189 Sennah. This type of research uses Research and Development using the ADDIE research model. Validation by material experts was carried out in one stage with a result of 75.38%, which is included in the "Feasible" category. Testing by media experts was carried out in two stages. In the first stage, 60% of the assessments were included in the category of quite feasible, with some suggestions for improvement. In the second stage, 80% of the assessments were included in the feasible category and did not require further revision. The results of the teacher response questionnaire showed an average percentage of feasibility of 91.4%, which was included in the "very practical" category. Meanwhile, the student response questionnaire obtained an average score of 95.45%. The effectiveness of interactive media is measured based on the average value of the pretest and posttest, which is measured using the N-Gain formula of 0.59, which is included in the effective category. The concluded that interactive media is feasible, practical, and effective.